Distinguishing science from pseudoscience in commercial respiratory interventions: an evidence-based guide for health and exercise professionals - Illidi, C. R.; Romer, L. M.; Johnson, M. A.; Williams, N. C.; Rossiter, H. B.; Casaburi, R.; Tiller, N. B. (European Journal of Applied Physiology, 2023)
Respiratory function has become a global health priority. Not only is chronic respiratory disease a leading cause of worldwide morbidity and mortality, but the COVID-19 pandemic has heightened attention on respiratory health and the means of enhancing it. Subsequently, and inevitably, the respiratory system has become a target of the multi-trillion-dollar health and wellness industry. Numerous commercial, respiratory-related interventions are now coupled to therapeutic and/or ergogenic claims that vary in their plausibility: from the reasonable to the absurd. Moreover, legitimate and illegitimate claims are often conflated in a wellness space that lacks regulation. The abundance of interventions, the range of potential therapeutic targets in the respiratory system, and the wealth of research that varies in quality, all confound the ability for health and exercise professionals to make informed risk-to-benefit assessments with their patients and clients. This review focuses on numerous commercial interventions that purport to improve respiratory health, including nasal dilators, nasal breathing, and systematized breathing interventions (such as pursed-lips breathing), respiratory muscle training, canned oxygen, nutritional supplements, and inhaled l-menthol. For each intervention we describe the premise, examine the plausibility, and systematically contrast commercial claims against the published literature. The overarching aim is to assist health and exercise professionals to distinguish science from pseudoscience and make pragmatic and safe risk-to-benefit decisions.